COVID-19-associated multisystem inflammatory syndrome in children (MIS-C) presenting as appendicitis with shock - Jamie E. Anderson; Julie A. Campbell; Lindsey Durowoju; Sarah L.M. Greenberg; Samuel E. Rice-Townsend; Kenneth W. Gow; Jeffrey Avansino (Elsevier, 2021)
Multisystem inflammatory syndrome in children (MIS-C) is an identified complication of the COVID-19 infection. A common presentation of both COVID-19 and MIS-C is acute abdominal pain, sometimes mimicking appendicitis. We report two cases of patients initially diagnosed with appendicitis who either presented with or developed signs of shock and were found to have MIS-C. An 8-year-old girl who tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) reverse transcriptase-polymerase chain reaction (RT-PCR) presented with fever, abdominal pain, and shock with ultrasound findings consistent with acute appendicitis. After being treated for MIS-C, she underwent appendectomy and improved. Final pathology was consistent with acute appendicitis. A 9-year-old girl who tested negative for COVID RT-PCR presented with uncomplicated appendicitis and underwent laparoscopic appendectomy, but developed post-operative fever and shock. Antibody testing was positive and she responded to treatment for MIS-C. Histology showed lymphohistiocytic inflammation within the muscularis propria, mesoappendix and serosa without the typical neutrophil-rich inflammation and mucosal involvement of acute appendicitis. The diagnosis was MIS-C, not appendicitis. Given the new reality of the COVID-19 pandemic, pediatric surgeons must be aware of MIS-C as a possible diagnosis and should understand the diagnostic criteria and current treatment guidelines.